Родовая дифференциация личинок V копеподитной стадии сем. Diaptomidae (Copepoda, Calanoida) - Степанова, Л.А. (Вестник зоологии, 1982)
Thoracic legs structure in fifth instar copepodite larvae of four species of Diaptomidae is described. At this stage, males Arctodiaptomus denticornis bear a generic character - short righ leg endopodite, A. salinus i s characteristic with a long appendix on left leg endopodite, Neutrodiaptomus angustilobus - with a short and thinlateral spur on right leg exopodite, and Eudiaptomus coeruleus - with equal length rounded left and right leg sendopodites. Arctodiaptomus females on this stage are distinct by the spur absence on fifth leg pairendopodite, Neutrodiaptomus females - by.acute endopodite bearing two spurs. In A. denticornis and E. coeruleus femalesendopodites are. Somewhat underdeveloped and essentially differ from those in N. angustilobus and A. salinus.